0539 The Effect Of Continuous Positive Airway Pressure Treatment On Abdominal Adiposity In Severe Obstructive Sleep Apnea: Evidence From Randomized, Active Controlled Trials. (12th April 2019) - Lin, Ming-Tzer; Lee, Pei-Lin; Yu, Chih-Wei; Shih Shih, Ting-Fang; Wu, Whey-Dong; Shau, Wen-Yi; Hsu, Huey-Jen; Huang, Kuo-Chin; Chen, Chi-Ling; Tang, Ching-Ting; Yu, Chong-Jen
Abstract: Introduction: The effect of continuous positive airway pressure (CPAP) on abdominal adiposity in severe obstructive sleep apnea (OSA) was inconclusive. The effect may be affected by confounders derived from subjects and study design. The present study aimed to test that if the effects of CPAP treatments on visceral adiposity in patients with severe OSA was influenced by subject characteristics, type of control, and parameters of CPAP treatment. Methods: Two double-blind, randomized, subtherapeutic-CPAP controlled trials was conducted. Trial I, 96 patients (consecutive OSA) were randomized to therapeutic or sub-therapeutic (3 cmH2 O) CPAP for 3 months. Trial 2, 24 male patients without comorbidities other than hypertension (healthy OSA) were randomized to therapeutic or sub-therapeutic (1cmH2 O) CPAP for 3 months. The abdominal adiposity was measured by magnetic resonance imaging at baseline and at the end of trials. The results of both studies were then meta-analyzed with other studies searched up to September 13rd 2018. Results: 64.6% in consecutive OSA had comorbidities and they were older and less sleepy than healthy OSA. After CPAP therapy, the reduction of the visceral fat was observed in healthy OSA (difference in change, -194.83 cm 3 ; 95% CI, -354.9 to -34.75 cm 3 ) while the reduction was not significant in consecutive OSA. Meta-analysis these 2 studies along with 4 other studies showed CPAP had no effect (mean difference, 0.77 cm 3 ; 95% CI, -21.07 to 22.60 cm 3 ). The subgroup analysis showed the increase of visceral fat was significant while CPAP treatment was less 3 months. The meta-regression showed younger, more obese, and longer duration of CPAP treatment was associated with more reduction of visceral adiposity. Conclusion: CPAP reduces visceral fat in patients with severe OSA who younger age, more obese, and longer duration of CPAP. Support (If Any): Ministry of Science and Technology (MOST 103-2314-B-002-139-MY3, NSC 100-2314-B-002-140-; NSC 101-2314-B-002-195-); National Taiwan University Hospital (NTUH 105-S2998)